E vamos a luta: o fazer do(a) psicólogo(a) no Centro de Referência Especializado de Assistência Social – CREAS - Melo, Eleonora Pereira (2011)
This paper aims to examine how is the doing of psychologists at the Center of Specialized Reference for Social Assistance (CREAS) in a municipality of the metropolitan region of Fortaleza – CE, Brazil, from the perception of them about their work. So it is considered as a theoretical reference, various official documents about the public policies for social assistance and others that provide parameters for the work of psychologists in the CREAS, as well as studies on the Clinic of the Activity without being excluded from the collaboration of other clinics such as the Psychodynamic of the Work, and also the knowledge of the Ergonomics. The investigations aims to analyze the official and/or not official documents, until then existing, that guide the actions of the psychologists in the field of welfare policies, specifically in the CREAS, and to know the actions taken by the psychologists in carrying out their work activities, by favoring the psychologists a process of interpretation of their activities and the impact of their work within the centers where they carry out their activities. For this research, methodological investigating arrangements of work situations are adopted based on the analysis of the work context of an approach of the resources of the simple autoconfrontation method and the method of the instructions for the double. The use of these resources, which is based on a study of observations and interviews with the psychologists involved in the municipality examined, was the way envisioned to account for the reality of the workplace and their professionals chosen. It is possible to understand the various dimensions that involve the activity of these professionals, and it is found that the collective of psychologists inserted in the specific CREAS is fragmented due to the difficulty of sharing experiences and implements. However, these psychologists still find, in the activities they perform, creating spaces, construction of meaning and pleasure achievements. This study has the merit to initiate a process of theoretical and empirical production of information that sought to contribute to a better understanding of the role of the psychologist in the CREAS, generating considerations that guided the maturation of the discussions on the role of a professional in a new area for the actions of Psychology. It is expected that, from here, firmer guidelines to make the psychologist may arise at this institution so as to guide the activities of professionals, their selection, evaluation of their actions and the development of skills more consistent with the reality of the work. Similarly, it is expected that new debates arise in order to make think, even of academic records of training psychology professionals, so that it can meet the demands imposed by these new workplaces for the psychologist, as well as the users of these services.